2015
DOI: 10.1080/1059924x.2015.1074633
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Using Electronic Health Records to Describe Demographic and Clinical Indicators of Migrant and Seasonal Farmworkers

Abstract: Few extensive, national clinical databases exist on the health of migrant and seasonal farmworkers (MSFWs). Electronic health records (EHRs) are increasingly utilized by Federally Qualified Health Centers (FQHCs) and have the potential to improve clinical care and complement current surveillance and epidemiologic studies of underserved working populations, such as MSFWs. The aim of this feasibility study was to describe the demographics and baseline clinical indicators of patients at an FQHC by MSFW status. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The results of the current study predicted that around 95% of the population agreed that EHR system would help in maintaining the dental and medical history, medication lists and patients’ demographic details. Consistent to it, Socias et al (2016) conducted a study to evaluate the feasibility of using EHRs to describe the demographic and clinical indicators of seasonal and migrant farmworkers. Thus, the study reported that EHR data have a significant positive impact on patient care; however, EHR needs to be improvised with regard to their quality and usability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study predicted that around 95% of the population agreed that EHR system would help in maintaining the dental and medical history, medication lists and patients’ demographic details. Consistent to it, Socias et al (2016) conducted a study to evaluate the feasibility of using EHRs to describe the demographic and clinical indicators of seasonal and migrant farmworkers. Thus, the study reported that EHR data have a significant positive impact on patient care; however, EHR needs to be improvised with regard to their quality and usability.…”
Section: Discussionmentioning
confidence: 99%
“…The study proved the efficiency of EHR by showing its production, application and utilisation of information in the health management systems. Another similar study conducted by Socias et al (2016) determined the feasibility of using EHRs in describing the demographic and clinical indicators of patients. The results showed EHRs to be key data source for occupational injury and illness surveillance and research by reaching the vulnerable population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…25,26 Currently, the most widely used occupational surveillance data sources likely substantially and systematically undercount certain work-related diseases and injuries, certain types of workplaces, and certain populations of workers. 27–29 The EHR provides new opportunities to improve surveillance by capturing cases seen by PCPs, especially for workers reluctant to report their case to workers’ compensation or to their employer or where the relation to work was not previously recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In further work, it has been found possible to utilise a workplace EHR for describing injuries in a worker population [31]. Many factors such as comorbidities, psychosocial and clinical factors that have been found relevant for describing injuries are the same as those that could be used for predicting outcomes in WMSDs.…”
Section: The Use Of Ehrs To Predict Outcomes To Wmsdsmentioning
confidence: 99%
“…Some aspects include missing data, unstructured data, interoperability issues between datasets and collection of the right data. Missing data is a challenge for many EHR studies [23], missingness of desirable research variables can be nearly half what is required [27,31]. Missing data is not, however, only a challenge for EHRs, and exists in claims databases [8,34,38,41] as well as in studies utilising patient questionnaires or PROMs [42,43].…”
Section: Sources Of Data For Predicting Outcomes To Wmsdsmentioning
confidence: 99%